Difference in operation of Mouse and Touchscreen in older adults - Anika Steinert; Marten Haesner; Julie Lorraine O`Sullivan; Elisabeth Steinhagen-Thiessen (International Journal of Serious Games, 2015)
Within the present study, an investigation with 50 older adults aged over 60 years was conducted. One aim of the study was to identify differences in usage of an internet platform for cognitive training with two different input devices. For this purpose, the subjects had to solve tasks on both PC and tablet computers. The success rate and the amount of time required to solve the tasks were recorded in a standardized manner. Additionally, participants were asked about the subjective advantages of both terminal devices and about their general preference. Overall, we found hardly significant differences in success rates and task-solving time. Contrary to other studies, where participants had to choose a defined target or perform a short specific task the older adults in the present study made nearly the same number of mistakes and needed almost the same time for solving the assigned tasks when using the PC and the tablet.